Effect of layout orientation on the performance and reliability of high voltage N-LDMOS in standard submicron logic STI CMOS process - Paulsen, Ron (2005 International Reliability Physics Symposium, 2005)
An N-LDMOS (N-channel laterally diffused drain MOSFET), fabricated in a standard CMOS process, is used to provide relatively high-voltage (HV/spl sim/12 V) capability without any extra process steps. However, there is very little information available for LDMOS devices with technologies below 0.35 /spl mu/m using STI isolation. In this work, we investigated the typical layout geometry dependence of device drain current leakage, drain breakdown and on-state current characteristics, with devices fabricated in a standard logic 0.18 /spl mu/m and 0.25 /spl mu/m process. Furthermore, for the first time, a dependence on layout orientation and its effect on hot-carrier injection (HCI) reliability are reported.